التعبير الحركي من خلال قانون الرسم ورؤية الفنان المصري القديم - حمزة، أحمد محي (جامعة حلوان - كلية التربية الفنية, 2019)
لقد استطاع الفنان المصري القديم أن يخلد ذكراه عبر التاريخ لما أنجزه من أعمال صرحية إبداعية مازالت شاهدة عليه وعلى إبداعه الفني والتقني وفي إطار تعرض البحث إلى موضوع التعبير الحركي من خلال قانون الرسم ورؤية الفنان المصري القديم "فكان على الباحث تناول الموضوع من خلال محاور بحثية محددة وهي التأكيد على ما تحويه رسوم المصري القديم من حس حركي وفني ينقلنا إلى عالم الحركة وديناميكيتها ومدى ارتباطها بقانون النسب ورؤية الفنان موضحا ذلك من خلال العديد من المفاهيم منها تعريف الرسم وقانون النسب بالإضافة إلى رؤية الفنان الإبداعية ومدى وعيه وفهمه للتعبير الحركي، وكان ذلك من خلال عدة تساؤلات منها هل فن الرسم فناً مستقلاً بذاته، أم أنه تحضيري لفنون أخرى، هل الفنان المصري القديم التزم بقانون النسب- الذي وضعه وأسسه- أم أن هناك بالإضافة إلى قانون النسب رؤية الفنان وما تحمله من وعي ثقافي وفلسفي، وهل أدرك الفنان المصري القديم الإحساس الحركي واستطاع التعبير عنه بدقة وإتقان، وجاءت الدراسة خلال الفترة من 2690 إلى 1085ق. م.
The Egyptian artist was able to commemorate his memory through history, because of the work of creative still witness to him and his artistic and technical and in the framework of the research presented to the subject of "motor expression through the law of drawing and the vision of the Egyptian artist old" was the researcher to address the subject through Specific research axes are the emphasis on the contents of ancient Egyptian drawings of a sense of movement and art, which brings us to the world of movement and its dynamics and its relevance to the law of descent and the vision of the artist, explaining this through many concepts including definition of drawing and law ratios in addition to the vision of the creative artist and the extent of consciousness and understanding of To the expression of the movement, and this was through several questions, including the art of drawing art independent of itself, or is it preparatory to other arts, is the Egyptian artist old committed to the law of descent - which he established - or is there in addition to the law of descent and the artist's vision and cultural awareness And philosophical, and did the Egyptian artist realized the old sense of movement and was able to express it accurately and mastery, and committed researcher study during the period from 2690 to 1085 BC
Keywords: فن الرسم -- التعبير الحركي -- قانون النسب -- الفن المصري القديم -- الفنان المصري القديم -- الرسوم المصرية القديمة